Socio-Economic and Political Development For Indian Women (With Special Reference to Women Empowerment): Promoting Gender Equality and Women's Empowerment in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Empowerment of women hasbecome one of the most important Concerns of 21st century not onlyat national level but also at the international level. Efforts by the Govt. areon to ensure Gender equality but Government initiatives alone would not besufficient to achieve this goal. Society must take initiative to create aclimate in which there is no gender discrimination and Women have fullopportunities of Self decision making and participating in the Social,Political and Economic life of the Country with a sense of equality. Then onlythe Vedic verse ;= ukjh iwT;Urs jeUrs r= nsork  (Wherever Women is respected, God resides there)would come true.